MUSCLE AND SKIN AMINO ACID COMPOSITIONS OF THE GREATER CANE RAT (THRYONOMYS SWINGERIANUS) - E.I. ADEYEYE; R.O. JEGEDE (International Journal of Pharma and Bio Sciences, 2010)
The Greater Cane Rat muscle and skin samples were evaluated for their amino acid profiles. The amino acid values were (in mg/g crude protein): highest concentrated amino acid was glutamic acid (150; muscle) and 140 (skin) with highest essential amino acid as leucine (72.2; muscle) and 69.0 (skin). Total essential amino acids (mg/g crude protein): 382(42.9 %) muscle and 350 (47.6 %) skin. The limiting amino acid on whole hen’s egg score was threonine (0.39; muscle) and serine (0.39; skin); on provisional scoring pattern, it was threonine (0.50) muscle and 0.75 (skin); on pre-school child requirement, it was threonine (0.59) in muscle but lysine (0.69) in skin. Significant differences existed between the amino acid profiles at r = 0.05 and n-2; total amino acid levels being 891 mg/g crude protein (muscle) and 736 mg/g crude protein (skin).